Strengthening Islamic Civilization History Literacy through Education on theDecline of the Three Great Islamic Empires - Wardiah Hamid; Syamzan Syukur; Susmihara Susmihara (Maslahah: Jurnal Pengabdian Masyarakat, 2026)
Limited public understanding of the rise and decline of the three major Islamic empires—the Ottoman Empire, the Safavid Empire, and the Mughal Empire—has resulted in the educational, leadership, and civilizational values embedded in their histories not being optimally utilized as learning resources. This Community Partnership Program (PKM) aimed to enhance participants' literacy on Islamic civilization and strengthen their understanding of the factors contributing to the rise and decline of these three empires as valuable lessons for contemporary Islamic education and society. The program was implemented through educational sessions, interactive lectures, group discussions, question-and-answer sessions, and participant evaluations. The target participants included community members, teachers, and students interested in the study of Islamic history. The results of the program demonstrated an improvement in participants' understanding of the historical development of the Ottoman, Safavid, and Mughal Empires, the factors influencing their growth and decline, and the relevance of these historical experiences to strengthening leadership values, character development, the advancement of knowledge, and lifelong learning. Participants also showed high enthusiasm throughout the activities and were able to relate historical lessons to the contemporary challenges of Islamic education. This Community Partnership Program contributed to improving Islamic historical literacy and encouraged the use of Islamic civilization history as a medium for character building and strengthening Islamic insight through contextual and value-based learning.